Efecto del lactosuero en la alimentación de pollos broiler con raciones bajas en proteínas (15% y 17%), en etapa de crecimiento y acabado - Paredes Tuanama, Luis Enrrique (2010)
Based on the results and the discussions in this research was conducted aiming to contribute to knowledge of an efficient and economic supply of chickens for meat in San Martin, for which we evaluated the use of whey protein supplement Broiler chickens, where it serves two low-protein rations (T1 and T2 = 15% = 17%) and control (20% PT) in the growing and finishing stages. Being able to determine that was not found in the three treatments studied statistically significant difference (P <0.05), taking the index parameters of the final weight (PVF) and weight gain (IP), in which no significant differences were reported although in both parameters T0 showed the highest values with a PVF = g. and IP = 1200.8 g, followed by T1 and T2 values of PVF = 1887.5 g. and 1861 g., e I.P = 1094.9 g. in T2 and 1086 g. in T1, respectively, verifying thus the beneficial effect of the use of whey protein supplement, to be offset low levels and quality of protein used in the rations of T1 and T2. Also note that the feed conversion ratio obtained in this study (T0 = 2.2, T1 = T2 = 2.05 and 2.05) are good, considering the expected values in broiler breeding to the seventh week, which tells us that rationing followed and practiced feeding management was optimal, and that the use of whey did not impair the use or digestive efficiency of birds. And also determined that the best use of whey generated economic benefits as observed in T1 and T2, which reported the highest rates of return (T1 and T2 = 24.5% = 24.7%) compared to the control (T0 = 23.1%).